An investigation of the determinants of energy intensity in emerging market countries - Xiangdong Sun (Elsevier, 2022)
With the rapid economic growth in most Emerging Market Countries, the energy intensity showed a striking decline. To explore this energy puzzle, we evaluated energy intensity reduction in 30 Emerging Market Countries, which were referred to as E30 in this paper. A combined conceptual analysis framework was proposed and two main procedures were involved: 1) the aggregate energy intensity of E30 was decomposed into activity mix and national intensity, applying the Logarithmic Mean Divisia Index (LMDI) approach; 2) regression analysis was used to assess the relationship between energy price and national intensity following Cobb–Douglas cost function, where the energy price of each country was measured using energy depletion and Brent oil price (as a robust check). The results indicated that national intensity was the main factor of aggregate energy intensity reduction with a contribution share of more than 100%, whether in 27 countries from 1971 to 2016 or 30 countries from 1990 to 2016. With respect to the impact of energy price on national intensity, we concluded that the relative energy price increased by more than 170% between 1971 and 2016. But the corresponding average decrease in national intensity was limited because the absolute value of negative elasticity between energy price and national intensity was less than 0.07. So, some energy-saving policies can also be used to achieve energy efficiency goals.